2008
DOI: 10.4028/www.scientific.net/kem.384.283
|View full text |Cite
|
Sign up to set email alerts
|

Electroplated Nickel Composites with Micron- to Nano-Sized Particles

Abstract: Abstract. Electroplated nickel coatings provide ductility, excellent corrosion resistance and good wear resistance, which qualifies them to meet complex demands of engineering, microtechnology and microelectronics. The co-deposition of particles is a promising alternative to deposit layers with adequate microstructure and properties avoiding the rise of residual stress. The incorporation of the sufficient quantity of particles, monodisperse distribution and downsizing to nanometre scale affect the amount of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
3
14
0
1
Order By: Relevance
“…2b), though the highest titania incorporation rate is achieved. Studies concerning the incorporation of TiO 2 nanoparticles in nickel under DC regime have shown that the dispersed nano-particles either increase the nucleation [6,12] or restrain the crystal size rather by inhibiting crystal growth than by providing new nucleation surfaces [14,15]. However, it seems that, under these PC conditions, pulse frequency is the main factor determining the average grain size of the Ni crystallites, diminishing the influence of the increased codeposited titania particles.…”
Section: Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…2b), though the highest titania incorporation rate is achieved. Studies concerning the incorporation of TiO 2 nanoparticles in nickel under DC regime have shown that the dispersed nano-particles either increase the nucleation [6,12] or restrain the crystal size rather by inhibiting crystal growth than by providing new nucleation surfaces [14,15]. However, it seems that, under these PC conditions, pulse frequency is the main factor determining the average grain size of the Ni crystallites, diminishing the influence of the increased codeposited titania particles.…”
Section: Effectmentioning
confidence: 98%
“…Specifically, TiO 2 particle-reinforced Ni composite electrodeposits exhibit improved mechanical properties [6][7][8][9][10][11][12], accompanied by an interesting photoelectrochemical [3] and electrocatalytical behaviour [13]. Moreover, literature survey has revealed that the incorporation of nano-sized TiO 2 particles into the nickel matrix, under direct current (DC) electrodeposition, leads to the formation of finer structures with reduced grain size [12,14,15], decreases the residual tensile stresses [12], increases the hardness [6][7][8][9][10][11][12], wear [9][10][11][12] and corrosion resistance [6,10,12] of the coatings, compared to pure Ni electrodeposits, although controversial results have been reported concerning corrosion resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are a considerable number of research reports concerning the effects of bath composition and operation conditions on the amount of inert particles codeposited with the metal matrix and the resulting properties of the composite coatings [1,2,4,5,[8][9][10]. However, limited research is carried on the effect of codeposited particles on the microstructure [1,2,10] and the correlation between structural characteristics and resulting properties [11].…”
Section: Introductionmentioning
confidence: 96%
“…TiO 2 dispersion-hardened metal electrocoatings show a clear increase of the hardness and wear resistance compared with the pure matrix ones [1][2][3][4][5][6][7][8][9][10]. There are a considerable number of research reports concerning the effects of bath composition and operation conditions on the amount of inert particles codeposited with the metal matrix and the resulting properties of the composite coatings [1,2,4,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation